DDR2‐mediated autophagy inhibition contributes to angiotensin II‐induced adventitial remodeling - Gaojian Huang; Zhilei Cong; Yuhao Zhao; Tong Zhu; Ruosen Yuan; Zhen Li; Xuelian Wang; Jia Qi (Clinical and Translational Medicine)
Abstract Aims Adventitial remodelling in hypertension is characterized by a transformation of adventitial fibroblasts (AFs) into myofibroblasts. Previous studies have highlighted the crucial role of discoidin domain receptor 2 (DDR2) in vascular remodelling. Since DDR2‐sustained tyrosine phosphorylation activates PI3K, which may inhibit autophagy through the mTOR signalling pathway, we aimed to investigate whether DDR2 contributes to mTOR‐mediated autophagy suppression and subsequently promotes AFs transformation and adventitial remodelling. Methods and results Single‐cell RNA sequencing revealed that DDR2 was upregulated in adventitial fibroblasts (AFs) in angiotensin II (Ang II, 1000 ng/min/kg) administrated wild‐type (WT) mice. In AFs, rapamycin, an autophagy agonist, significantly attenuated Ang II‐induced autophagy suppression and phenotype switching, whereas the autophagy inhibitor chloroquine (CQ) exacerbated these effects. DDR2 inhibition significantly alleviated PI3K/Akt/mTOR pathway‐mediated autophagy suppression and subsequently inhibited AFs phenotypic switching. Conversely, DDR2 overexpression aggravated autophagy suppression and AFs phenotypic switching. Consistent with the cellular findings, prophylactic administration of rapamycin (4 mg/kg/d) or conditional knockout of Ddr2 in mice ameliorated autophagy suppression, AFs differentiation and adventitial remodelling in vivo. Conclusion DDR2 serves as a critical mediator of autophagy suppression during Ang II‐induced phenotypic transformation of AFs and adventitial remodelling. Targeting DDR2 signalling attenuates autophagy dysfunction and inhibits AFs activation, thereby mitigating pathological adventitial remodelling. These findings highlight DDR2 as a potential therapeutic target for preventing conditions driven by aberrant adventitial remodelling.